Production Potential of Sophore Barb (Puntius sophore) in Polyculture - A Field Trial in Tripura - Debnath, Chandan; Sahoo, Lopamudra; Datta, M; Ngachan, S V (Fishery Technology, 2025)
An experiment was conducted on the polyculture of sophore barb with carps in the farmers’ pond of Dhalai Tripura to evaluate the production performance and feasibility of carp-barb culture. Two treatments were tried with three replicates for each kind. Catla catla, Labeo rohita and Cirrhinus mrigala were stocked solely at the rate of 9500 fingerlings ha-1 in the treatment-1 as control, whereas in treatment-2, Puntius sophore was stocked at the rate of 25 000 ha-1 in addition to carps. The stocking size was 9.23, 9.06, 6.63 and 3.26 respectively for catla, rohu, mrigal and barb. The average fish production over a period of 210 days was recorded as 2132 and 2115 kg ha-1 in treatment-1 and treatment-2 ponds, respectively. The overall fish production was found to be same without significant difference between the treatments. Apparently the growth of carps was lowered in the presence of barb, but the overall production can be improved by following better management practices. Partial harvesting of barb is a prerequisite to maintain compatible existence among carps and small fish.